CCR5+T-bet+FoxP3+ Effector CD4 T Cells Drive Atherosclerosis. Issue 10 (13th May 2016) - Li, Jie; McArdle, Sara; Gholami, Amin; Kimura, Takayuki; Wolf, Dennis; Gerhardt, Teresa; Miller, Jacqueline; Weber, Christian; Ley, Klaus
Abstract : Rationale: : CD4 T cells are involved in the pathogenesis of atherosclerosis, but atherosclerosis-specific CD4 T cells have not been described. Moreover, the chemokine(s) that regulates T-cell trafficking to the atherosclerotic lesions is also unknown. Objective: : In Apoe −/− mice with mature atherosclerotic lesions (5 months of high fat diet), we find that most aortic T cells express CCR5 and interferon-γ with a unique combination of cell surface markers (CD4 + CD25 − CD44 hi CD62L lo ) and transcription factors (FoxP3 + T-bet + ). We call these cells CCR5Teff. We investigated the role of CCR5 in regulating T-cell homing to the atherosclerotic aorta and the functionality of the CCR5Teff cells. Methods and Results: : CCR5Teff cells are exclusively found in the aorta and para-aortic lymph nodes of Apoe −/− mice. They do not suppress T-cell proliferation in vitro and are less potent than regulatory T cells at inhibiting cytokine secretion. Blocking or knocking out CCR5 or its ligand CCL5 significantly blocks T-cell homing to atherosclerotic aortas. Transcriptomic analysis shows that CCR5Teff cells are more similar to effector T cells than to regulatory T cells. They secrete interferon-γ, interleukin-2, interleukin-10, and tumor necrosis factor. Adoptive transfer of these CCR5Teff cells significantly increases atherosclerosis. Conclusions: : CCR5 is specifically needed for CD4 T-cell homing to the atherosclerotic plaques. CCR5 + CD4 T cells express an unusual combination of transcription factors, FoxP3 and T-bet. Although CCR5Teff express FoxP3, we showed that they are not regulatory and adoptive transfer of these cells exacerbates atherosclerosis. Abstract : Supplemental Digital Content is available in the text.